Oxygenation targets in ICU patients with COVID‐19: A post hoc subgroup analysis of the HOT‐ICU trial. Issue 1 (20th September 2021) - Rasmussen, Bodil S.; Klitgaard, Thomas L.; Perner, Anders; Brand, Björn A.; Hildebrandt, Thomas; Siegemund, Martin; Hollinger, Alexa; Aagaard, Søren R.; Bestle, Morten H.; Marcussen, Klaus V.; Brøchner, Anne C.; Sølling, Christoffer G.; et al.
Abstract: Background: Supplemental oxygen is the key intervention for severe and critical COVID‐19 patients. With the unstable supplies of oxygen in many countries, it is important to define the lowest safe dosage. Methods: In spring 2020, 110 COVID‐19 patients were enrolled as part of the Handling Oxygenation Targets in the ICU trial (HOT‐ICU). Patients were allocated within 12 h of ICU admission. Oxygen therapy was titrated to a partial pressure of arterial oxygen (PaO2 ) of 8 kPa (lower oxygenation group) or a PaO2 of 12 kPa (higher oxygenation group) during ICU stay up to 90 days. We report key outcomes at 90 days for the subgroup of COVID‐19 patients. Results: At 90 days, 22 of 54 patients (40.7%) in the lower oxygenation group and 23 of 55 patients (41.8%) in the higher oxygenation group had died (adjusted risk ratio: 0.87; 95% confidence interval, 0.58–1.32). The percentage of days alive without life support was significantly higher in the lower oxygenation group ( p = 0.03). The numbers of severe ischemic events were low with no difference between the two groups. Proning and inhaled vasodilators were used more frequently, and the positive end‐expiratory pressure was higher in the higher oxygenation group. Tests for interactions with the results of the remaining HOT‐ICU population were insignificant. Conclusions: Targeting a PaO2 of 8 kPa may be beneficial in ICU patients with COVID‐19. These results come with uncertainty due to the low number of patients in this unplanned subgroup analysis, and insignificant tests for interaction with the main HOT‐ICU trial. Trial registration number: ClinicalTrials.gov number, NCT03174002. Date of registration: June 2, 2017.